An update on morphology and distribution of Ruppia filifolia (Philippi) Skottsberg in the Magellan region, southern Chile - Murcia, Silvia; Terrados, Jorge; Ramírez-García, Pedro; Mansilla Muñoz, Andres Omar (My University, 2018)
ABSTRACT Vegetative and reproductive morphology of Ruppia filifolia (Philippi) Skottsberg is updated and completed by examining natural specimens, reviewing the literature, comparing to specimens from different locations and generating new iconography of the species from waters across the Magellan region, Subantarctic Chile. We expand current knowledge on morphology (rhizome-root, branching, foliage, inflorescence, fruit, habits) and geographical distribution of R. filifolia in Austral South America, with the addition of six new localities for the taxon in Chile. Our results are used to identify this macrophyte and to distinguish it from R. maritima after some authors reported their co-occurrence in the southern tip of South America, leading to taxonomic confusion. Also, the new information on R. filifolia distribution in the Magellan region broadens the research on a neglected seagrass. In the Southern Hemisphere, contrary to global trends of seagrass ecosystems decline, new niche distributions are opening up in southernmost Chile, reflecting environmental changes.
Keywords: seagrass; iconography; exsiccate; geographic allocation; subantarctic waters; magellan region